The Hidden Sufferers: Parental Reactions to Childhood Cancer during Treatment and at Survival. (27th June 2017) - Castellano-Tejedor, Carmina; Blasco-Blasco, Tomás; Pérez-Campdepadrós, Marta; Capdevila, Lluis
Abstract: This study was twofold: 1) to assess parental reactions to childhood cancer throughout the oncological experience and 2) to explore associations between parents' reactions during treatment and cancer-related distress at survival. A cross-sectional descriptive study collecting data (at survival) from retrospective (perceived social support, optimism, distress, coping in the worst situation) and current variables (general stress, distress regarding cancer, benefit finding) was carried out. Forty-one parents of childhood cancer survivors were assessed. High levels of distress ( M = 9.5, SD = 1.32, range 4-10) and self-reported efforts to overcome difficulties occurring during the hospitalization ( M = 7.48, SD = 3.01, range 0-10) were found. However, parents received high social support from very different sources. This could explain the satisfactory levels of optimism found (43.9% of the sample, M ≥ 16, range 9 – 24). Most parents reported to use engagement ( M = 2.57, SD = 0.41, range 1-4) and help-seeking ( M = 2.52, SD = 0.53, range 1-4) coping strategies to overcome difficulties. Some parents recognized to use psychological defenses when coping with the distress of cancer. However, this disengagement style was less preferred ( M = 1.62, SD = 0.37, range 1-4). Finally, 22% of parents reported positive consequences and 60% reported positive and negative consequences too. When exploring how treatment experiences can influence cancer-related distress in survivorship, we observed that those who received less social support used more disengagement coping and referred higher efforts to overcome difficulties during treatment, displayed persistent distress at survival. These same parents showed higher scores on general stress. Besides, these results were not influenced by child's sequelae at survival. These findings support the hypothesis that "the end of treatment is not the end". Consequently, special attention should be placed in screening parents experiences throughout different milestones of cancer to design tailored interventions aimed at reducing persistent distress at survival.